PENGENDALIAN MUTU PADA PENGOLAHAN MINYAK SAWIT PADA PT. HUTAN HIJAU MAS BERAU - Asri anto; Zainal Ilmi; Ike Purnamasari (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
This study obtains to determine quality graphics of Crude Palm Oil (CPO) during the month of March 2016 and carrying out quality control using statistical quality control’s tool. Quality control analysis was performed using statistical tools histograms, pareto chart and fishbone diagram. Histograms are used to present the data is in order to make it easier to understand the the data for subsequent analysis. Then the identification of the types of defects are dominant using pareto diagram. The next step is to look for factors that cause damage to the product using a causal diagram can then be prepared for a recommendation or a proposal of quality improvement.The results indicate that the output of CPO were in a state of uncontrolled or still experiencing irregularities. It can be seen on a bar diagram of the which point the fluctuating and irregular, and many are out of the control limits. Based on the Pareto diagram, of the three conditions CPO quality improvement priority needs to be done is for the type of impurity content. From the analysis of the causal diagram can be seen the factors causing disability derived from human factors / workers, production machinery, work methods, materials / raw materials and work environment, so that the company can take preventative measures and improvements to reduce the level of disability and improve product quality.Keywords: Quality Control, Statistical Quality Control, Histogram